2018
DOI: 10.1136/lupus-2018-000267
|View full text |Cite
|
Sign up to set email alerts
|

Progression of subclinical and clinical cardiovascular disease in a UK SLE cohort: the role of classic and SLE-related factors

Abstract: ObjectivesWe aimed to describe the rate and determinants of carotid plaque progression and the onset of clinical cardiovascular disease (CVD) in a UK SLE cohort.MethodsFemale patients with SLE of white British ancestry were recruited from clinics in the North-West of England and had a baseline clinical and CVD risk assessment including measurement of carotid intima–media thickness (CIMT) and plaque using B-mode Doppler ultrasound. Patients were followed up (>3.5 years after baseline visit) and had a repeat car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
(38 reference statements)
2
25
3
Order By: Relevance
“…In this sense, we only analyzed the data on the presence of carotid plaque. Our SLE population had a similar prevalence of carotid plaque (21.1% vs 16% to 37%) than what was reported in previous series of SLE patients (24,25). Patients with carotid plaque were more hypertensive and dyslipidemic than those without plaque.…”
Section: Discussionsupporting
confidence: 77%
“…In this sense, we only analyzed the data on the presence of carotid plaque. Our SLE population had a similar prevalence of carotid plaque (21.1% vs 16% to 37%) than what was reported in previous series of SLE patients (24,25). Patients with carotid plaque were more hypertensive and dyslipidemic than those without plaque.…”
Section: Discussionsupporting
confidence: 77%
“…Taking into consideration the high burden of CV risk factors in patients with SLE, this finding is of major importance because it suggests that excess progression of cIMT in SLE could be halted and argues for the concept of possibility to change the disease prognosis in SLE by applying improved monitoring, therapeutic and preventive strategies 21. It should be emphasised that the rate of antimalarial use in this cohort (about 90%) compares favourably with many other published cohort studies (35%–70%),22–25 which could account for some of the lower cIMT progression in the patients with SLE in this study. Further, frequent usage of preventive medication with antihypertensives, statins and low-dose aspirin may also contribute to favourable evolution of cIMT in these patients.…”
Section: Discussionmentioning
confidence: 58%
“…It is interesting to note that cIMT progression in this cohort was similar between the patients and the control population, yet the number of CV events during the 7-year follow-up was higher in the patients with SLE. In a study of 200 patients with SLE who were recruited from the clinics in England and had a baseline clinical and CV risk assessment including carotid ultrasound measures, neither presence of carotid plaque nor cIMT at baseline predicted future events after a median of 6 years, but higher triglycerides, ‘ever’ exposure to cyclophosphamide and the damage index independently predicted CV disease events 22. Possible explanations for this could be that in SLE, risk factors for the initiation of atherosclerosis may be different to those important for progression and severity of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In SLE, autoimmunity is perpetuated by defective clearance of apoptotic waste and immune complexes, along with disrupted lymphocyte biology and interferon pathways [3]. In addition, atherosclerosis has a great influence on morbidity and mortality in SLE [4]. Risk factors for the development of cardiovascular (CV) disease include both traditional risk factors, such as hyperlipidaemia, hypertension, diabetes, obesity, and smoking, together with SLEspecific factors, such as antiphospholipid antibodies and glucocorticoid therapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, atherosclerosis has a great influence on morbidity and mortality in SLE [4]. Risk factors for the development of cardiovascular (CV) disease include both traditional risk factors, such as hyperlipidaemia, hypertension, diabetes, obesity, and smoking, together with SLEspecific factors, such as antiphospholipid antibodies and glucocorticoid therapy [4]. Endothelial function is also impaired: a recent study found that brachial artery endothelium-dependent flow-mediated dilation (baED-FMD), an example of a biophysical marker of endothelial function, was decreased in SLE patients without obvious cardiovascular disease [5].…”
Section: Introductionmentioning
confidence: 99%